Cavitation Effect towards Graphene Oxide Synthesis Using Liquid Phase Exfoliation Method Assisted by Linear Alkylbenzene Sulfonate: Duwi Susanto, Salsabila Husna, Wipsar Sunu Brams Dwandaru - Duwi Susanto; Salsabila Husna Husna; Wipsar Sunu Brams Dwandaru Brams Dwandaru (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
In this study, graphene oxide was synthesized using the liquid phase exfoliation method. Graphene oxide synthesis was carried out by dispersing graphite powder in deionized water and adding linear alkylbenzene sulfonate surfactant, followed by exposure to ultrasonic waves at a frequency of 21 kHz. The graphite exfoliation process in this method took advantage of the cavitation phenomenon that occurred during the sonication process. The cavitation effect in this research was observed based on the characterization results of graphene oxide.